Understanding childhood obesity in Pakistan: exploring the knowledge, attitudes, practices of mothers, and influential factors. A cross-sectional study - Hudaib, Muhammad; Hussain, Laraib; Nazim, Laiba; Mohi Uddin, Sumaira; Jamil, Muhammad Usama; Bham, Shireen Qassim; Malik, Hurais; Rehman, Abdul; Malik, Usaid; Manahil; Umais Ahad, Ahmad; Mughal, Sanila; et al. (Frontiers in Public Health, 2024)
BackgroundChildhood obesity is a significant public health issue with far-reaching implications. The World Health Organization reported that in 2020, around 38 million children under five were overweight or obese globally, and in 2016, 340 million children and adolescents aged 5–19 were affected. In Pakistan, the situation is alarming; 66.9% of school-going children in Punjab were overweight, and 5.8% were obese in 2022. This study explores mothers’ knowledge, attitudes, and practices regarding childhood obesity in Pakistan and identifies factors contributing to this epidemic. Maternal perspectives are crucial as they significantly influence children’s dietary habits, physical activity, and attitudes toward food and body image.MethodsA cross-sectional study was conducted from November 2023 to January 2024 at four medical centers: Fazaia Ruth Pfau Medical College Hospitals Karachi, Baqai Medical University Karachi, and Nishtar Medical University Multan. The study included 191 mothers with children aged 5 to 15 years. Data were collected using a structured questionnaire on sociodemographic characteristics, knowledge, attitudes, practices, and perceptions of childhood obesity. IBM-SPSS version 26.0 was used for data analysis, employing statistical tests like Kruskal-Wallis, Mann–Whitney U, Spearman, or Kendall Tau correlation to examine associations.ResultsAmong the 191 mothers, 48.7% had education beyond intermediate, and 86.9% were housewives. The children’s BMI distribution showed that 27.7% were obese and 21.5% overweight. Mothers had moderate knowledge (60.5%) about childhood obesity; 75.4% recognized its long-term health risks, and 62.8% associated it with diabetes. Attitudes were generally positive, with a 78.5% average score. Most mothers (73.8%) believed obesity could be controlled and had healthy practices (70.1% average score). However, 96.9% reported witnessing stigmatization of obese children, and 79.6% felt pressured by relatives about their child’s weight.ConclusionThe findings indicate that while Pakistani mothers have moderate knowledge and positive attitudes toward childhood obesity, their practices are influenced by educational and socioeconomic factors. Addressing these disparities, enhancing public health initiatives, and mitigating stigmatization could improve childhood obesity management in Pakistan.